2016
DOI: 10.18632/oncotarget.14331
|View full text |Cite|
|
Sign up to set email alerts
|

Increased autophagy in fibroblast-like synoviocytes leads to immune enhancement potential in rheumatoid arthritis

Abstract: The incidence of rheumatoid arthritis (RA) has been reported to be correlated with a disorder of immunregulation. Rheumatoid arthritis fibroblast-like synoviocytes (RA-FLSs) play an important role in regulating the local immune microenvironment. However, the potential mechanism of RA-FLS in regulating the immnue response is not clearly understood. In this study, we demonstrated that the expression of HIF-1α was significantly up-regulated in rheumatoid arthritis tissue which indicated that the hypoxia condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Autophagy has been shown to engage in a complex interplay with apoptosis, and the inhibition of autophagy reportedly induces apoptosis in several cancer cell types 48 , 49 . Moreover, autophagy inhibitors effectively inhibit the immune activation function of RA-FLS medicated by IL-6, and anti-apoptosis effects induced by IL-17 are restored by autophagy inhibition 50 , 51 . Our results showed that silibinin suppressed autophagy in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 98%
“…Autophagy has been shown to engage in a complex interplay with apoptosis, and the inhibition of autophagy reportedly induces apoptosis in several cancer cell types 48 , 49 . Moreover, autophagy inhibitors effectively inhibit the immune activation function of RA-FLS medicated by IL-6, and anti-apoptosis effects induced by IL-17 are restored by autophagy inhibition 50 , 51 . Our results showed that silibinin suppressed autophagy in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 98%
“…Further pathway examples include glucose-6-phosphate isomerase (G6PI) [ 15 ], HIF-1α [ 16 ] and TNFα [ 17 ], which mediate hypoxia-induced angiogenesis, contributed to pannus formation in RA synovia. Furthermore, plenty of activated signaling pathways promote the secretion of inflammatory factors and aggravated immune response [ 18 , 19 ]. Particularly, regulators of extracellular matrix (ECM), such as MMPs [ 20 , 21 ], which enhanced the invasiveness of FLSs, are regarded as the “killer” of joint destruction.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is involved in the induction and suppression of inflammation and vice versa [ 6 8 ]. Proinflammatory cytokines such as tumor necrosis factor (TNF)-α and interleukin (IL)-6 have been shown to stimulate autophagy, and autophagy also contributes to the secretion of these cytokines [ 9 12 ]. However, autophagy is tightly regulated in its response to inflammation, such as participating in the clearance of protein complexes (e.g., inflammasomes) through proteasomal degradation [ 13 ].…”
Section: Introductionmentioning
confidence: 99%